Social support, impression management and well-being following a disaster: A literature review and some conceptual considerations - Rahaman, Nur Haffiza; Mustaffa, Che Su; Ariffin, Mohd Taib (2014)
In this paper, the influence of social support and impression management on the well-being of flood victims in Malaysia will be discussed.The paper starts with a definition of all the variables. Literature review so far shows that there is a limited research on victims of flood disaster in Malaysia.This paper will explore perceptions of flood victims toward social support provided by the government and analyze flood victims’ well-being and impression management.Finally, a conceptual framework will be proposed in accordance with the flood situation in Malaysia.The conceptual framework includes three main ideas, namely social support, impression management and well-being.This paper contributes to the study of disaster by providing a conceptual framework, which can be used to further investigate variables that influenced well-being because of disaster.